Embolization of a pseudo aneurism of the cystic artery secondary to acute cholecystitis - Ramírez, Enrique (2023)
We present the case of a 55-year-old male patient with a history of acute cholecystitis who presented during his hospitalization haemobilia due to a pseudoaneurysm of the cystic artery. Embolectomy of the cystic artery with polyvinyl alcohol microparticles was performed stopping the bleeding.